2011
DOI: 10.1038/jid.2010.404
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Function of the Natural Cytotoxicity Receptor NKp46 on Circulating Malignant CD4+ T Lymphocytes of Sézary Syndrome Patients

Abstract: The natural cytotoxicity receptors NKp30, NKp44, and NKp46 were identified as activating receptors mainly expressed by natural killer (NK) lymphocytes. In this study we show that peripheral blood malignant CD4(+) T lymphocytes from patients with Sézary syndrome, an aggressive form of cutaneous T-cell lymphoma, express NKp46 at their cell surface. Although NKp46 does not behave as an independent functional receptor, its engagement provides a strong inhibiting signal on the malignant T lymphocyte CD3-induced pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
3
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 29 publications
0
35
3
1
Order By: Relevance
“…Although the number of T-cell neoplasms included in our study is too low to provide statistical significance as to the sensitivity or specificity of aberrant CD335 expression for diagnosing T-cell neoplasia, it is noteworthy that aberrant dim expression of CD335 surface protein and aberrant NCR1 gene transcript was also recently reported in Sézary syndrome, MF, and T-LGL leukemia by other investigators. [45][46][47] Although we did not observe detectable CD335 expression by flow cytometry on the Sézary syndrome cases included in our study, this may be due to differences in technical staining parameters in our study compared with that by Bensussan et al, 45 who reported very weak surface CD335 expression on Sézary cells. Regardless, these collective data point to the aberrant acquisition of CD335 as a potentially unique marker of T-cell neoplasia in comparison with the loss of pan-T-cell antigens for which the loss of expression does not necessarily equate to neoplasia.…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…Although the number of T-cell neoplasms included in our study is too low to provide statistical significance as to the sensitivity or specificity of aberrant CD335 expression for diagnosing T-cell neoplasia, it is noteworthy that aberrant dim expression of CD335 surface protein and aberrant NCR1 gene transcript was also recently reported in Sézary syndrome, MF, and T-LGL leukemia by other investigators. [45][46][47] Although we did not observe detectable CD335 expression by flow cytometry on the Sézary syndrome cases included in our study, this may be due to differences in technical staining parameters in our study compared with that by Bensussan et al, 45 who reported very weak surface CD335 expression on Sézary cells. Regardless, these collective data point to the aberrant acquisition of CD335 as a potentially unique marker of T-cell neoplasia in comparison with the loss of pan-T-cell antigens for which the loss of expression does not necessarily equate to neoplasia.…”
Section: Discussioncontrasting
confidence: 76%
“…48,49 Alternatively, agonistic ligation of CD335 may also be useful to augment NK cell effector functions in various settings such as viral infection or allo-HSCT for AML. Interestingly, Bensussan et al 45 reported decreased TCR-induced proliferation of CD335+ neoplastic Sézary cells upon engagement of the aberrantly expressed CD335 receptor due to decreased phosphorylation of the CD3z subunit, suggesting that agonistic ligation of CD335 on neoplastic T cells may also be clinical useful. Preclinical trials would therefore be useful to…”
Section: Discussionmentioning
confidence: 97%
“…The presence of such biomarker (s) will aid in diagnosis and monitoring of the disease as well as in designing effective treatments targeting malignant cells and sparing of normal immunocompetent cells. Several surface molecules, namely NKp46, syndycan 4 (SD-4), ganglioside GD3 (CD60), mucin 1 (Muc 1) and CD158k/KIR3DL2 have been found to be highly expressed on CD4 + T cells from some SS patients compared with healthy controls [5, 9, 19, 36, 37]. SD-4, CD60 and Muc-1 molecules are also upregulated on activated normal CD4 + T cells [1, 8, 27].…”
Section: Introductionmentioning
confidence: 99%
“…A cytomorphological and immunophenotypical examination of the peripheral blood lymphocytes to identify circulating Sézary cells were performed in each case of epidermotropic T-cell lymphoma. [21][22][23] At baseline (at the time of diagnosis, or of any large-cell transformation) and three months after allogeneic HSCT, all patients underwent a staging computed tomography or positron emission tomography/computed tomography scan, and any abnormal lymph node was characterized histologically by an excisional biopsy. Pre-transplant global disease response was defined by comparing the disease status immediately prior to HSCT to the disease status before the onset of the last systemic treatment line before HSCT.…”
Section: Base-line Pre-transplant and Post-transplant Assessmentsmentioning
confidence: 99%